Formulation and Evaluation of Moringa Leaves Extract (Moringa oleifera L. ) Lotion with Variation Concentration of Triethanolamin - Marlina Indriastuti; Panji Wahlanto; Ditha Septya Utami (Ad-Dawaa : Journal of Pharmacy, 2023)
The Indonesian people know the moringa plant as a plant for consumption as a vegetable, a fetid decoction as well as animal feed. However, the Moringa plant, especially in the leaves, has another benefit , namely as an antioxidant. Antioxidants in Moringa leaves contain tannins, flavonoids, saponins, alkaloids, steroids and terpenoids. The purpose of this study was to determine a good formulation for the preparation of moringa leaf extract lotion with variations in the concentration of triethanolamine. The research method used is the experimental method. Data analysis was performed using the One Way Anova and Kruskal Wallis Test statistical methods . The results showed that the organoleptic test of slightly thick texture preparations for formula I, thick texture for formulas II and III; typical preparation odor of Moringa leaf extract; the color of the preparation is yellow. Homogeneity test of formula I was not homogeneous, formula II was not homogeneous in the third replication, formula III was homogeneous. The average viscosity test for formula I was 1,800 c.Ps, formula II was 8,300 c.Ps, formula III was 1,666 c.Ps. The average pH test for formula I was 6, formula II was 7, formula III was 8. The average adhesion test for formula I was 02.76 seconds, formula II was 02.02 seconds, formula III was 01.37 seconds. The average spreadability test for formula I was 3.9 cm, formula II was 6.6 cm, formula III was 6.9 cm. Based on the evaluation results obtained, it can be concluded that the triethanolamine concentration of 2.5% produces a good formulation for lotion preparations.